1996
DOI: 10.1111/j.1476-5381.1996.tb15174.x
|View full text |Cite
|
Sign up to set email alerts
|

An isobolographic analysis of the effects of N‐methyl‐D‐aspartate and NK1 tachykinin receptor antagonists on inflammatory hyperalgesia in the rat

Abstract: 1The interaction between N-methyl-D-aspartate (NMDA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

1997
1997
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(16 citation statements)
references
References 61 publications
(102 reference statements)
1
15
0
Order By: Relevance
“…These data suggest that an SP-mediated thermal allodynia does not develop in the setting of inflammation. Although this conclusion is somewhat at odds with the study of Ren et al (1996), which reported that NK-1 antagonists attenuate hyperalgesia to thermal stimulation in CFA-treated rats, it is consistent with the report of Liu and Sandkühler (1995), which found enhanced responses of lamina I neurons to mechanical, but not to thermal, skin stimuli during superfusion with SP.…”
Section: Nk-1 Receptor Internalization In the Setting Of Inflammationsupporting
confidence: 87%
“…These data suggest that an SP-mediated thermal allodynia does not develop in the setting of inflammation. Although this conclusion is somewhat at odds with the study of Ren et al (1996), which reported that NK-1 antagonists attenuate hyperalgesia to thermal stimulation in CFA-treated rats, it is consistent with the report of Liu and Sandkühler (1995), which found enhanced responses of lamina I neurons to mechanical, but not to thermal, skin stimuli during superfusion with SP.…”
Section: Nk-1 Receptor Internalization In the Setting Of Inflammationsupporting
confidence: 87%
“…In addition, thermal hyperalgesia in rats or mice with rheumatoid arthritis has been reported by others (Andrew and Greenspan, 1999;Ren et al, 1996;Inglis et al, 2007a,b). However, thermal hyperalgesia was not observed in PIA rats.…”
Section: Discussionmentioning
confidence: 83%
“…Moreover, increased distribution of neurons showing NK-1 receptor internalization was observed following noxious stimulation, with noxious stimulation induced NK-1 receptor internalization in deep dorsal horn neurons, instead of only in lamina I neurons as observed in untreated controls (Abbadie et al, 1997). Moreover, intrathecal administration of the NK-1 antagonist L-732,138 reverses inflammation-induced hyperalgesia (Birch et al, 1992;Gao et al, 2003;Ren et al, 1996;Traub, 1996). NK-1 receptor knockout mice showed decreased sensitivity to inflammation-induced pain, showing decreased nociceptive behaviors during the second phase of the formalin response and reduced FOS-positive neurons within the spinal cord following formalin injection into the hindpaw (De Felipe et al, 1998) as well as reduced mechanical hypersensitivity following intraplantar Mycobacterium tuberculosus (Kidd et al, 2003).…”
Section: Discussionmentioning
confidence: 92%